PEMANFAATAN GAS METANA DARI LIMBAH CAIR SEBAGAI SUMBER ENERGI - Febijanto, Irhan (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2017)
Utilization of biogas generated from wastewater of Palm Oil Mills (POM) is one of the alternative renewable energy which has a huge potential.Ã‚ This potential is supported by about 700 of POMs owned by private companies or state own company which scattered in Sumatera, Kalimantan and Sulawesi, mainly. Utilization of biogas as an electricity contributes to increase ratio of renewable energy utilization. However, there is a change of selling electricity price according to Ministerial Decree of Energy and Mineral Resource of Republic of Indonesia No.:12/2017, which the price is not determined based on the FIT (Feed in Tariff) anymore. New price is based on Cost Production of Power Plant (BPP) and it leads to a decline in the economy rate of biogas power plant. Therefore, investors become uninterested for developing biogas power plant in the future. Potential additional revenue from selling palm kernel was studied. An excess biogas is used to substitute palm kernel shell as boiler fuel of POM, and the substituted shell is sold to the market. The additional revenue from selling the shell increased economy rate of the biogas power plant. It is shown that IRR=7,21% increased to 14.43%. Keywords: Biogas Power Plant, wastewater, component price, methane gas.